The roles of IL-19 and IL-20 in the inflammation of degenerative lumbar spondylolisthesis - Kuo-Yuan Huang; Yu-Hsiang Hsu; Wei-Yu Chen; Hui-Ling Tsai; Jing-Jou Yan; Jung-Der Wang; Wen-Lung Liu; Ruey-Mo Lin (BMC, 2018)
Abstract Background Degenerative lumbar spondylolisthesis (DLS) is a major cause of spinal canal stenosis and is often related to lower back pain. IL-20 is emerging as a potent angiogenic, chemotactic, and proinflammatory cytokine related to several chronic inflammatory bone disorders likes intervertebral disc herniation, rheumatoid arthritis (RA), osteoporosis, and bone fracture. IL-19 also acts as a proinflammatory cytokine in RA. The aim of the present study was to investigate whether IL-19 and IL-20 are involved in DLS and compare three different tissues including disc, facet joint, and ligamentum flavum of patients with DLS to verify which tissue is affected more by inflammation. Methods Disc, facet joint and ligamentum flavum from 13 patients with DLS was retrieved, and the expression pattern of IL-19, IL-20, IL-20R1, IL-20R2, TNF-α, IL-1β, and MCP-1 was evaluated using immunohistochemical staining with specific antibodies. The disc cells were isolated and incubated with IL-19 and IL-20 under CoCl2-mimicked hypoxic conditions to analyze the proinflammatory cytokine expression pattern using real-time quantitative PCR with specific primers. Results IL-19 and IL-20 were positively stained and accompanied by abundant expression of TNF-α, IL-1β, and MCP-1 in facet joints of DLS patients. IL-19 and IL-20's receptors (IL-20R1 and IL-20R2) were expressed on chondrocytes and fibrocytes/fibroblasts in facet joint and ligamentum flavum tissues from patients with DLS. There was a significant correlation between the expression of IL-20 and IL-1β in facet joint. In vitro assay, IL-19 and IL-20 upregulated the expression of IL-1β, IL-6, TNF-α, IL-8, VEGF, and MCP-1 in primary cultured DLS disc cells under CoCl2-mimicked hypoxic conditions. Conclusions IL-19, IL-20, and their receptors as well as proinflammatory cytokines (TNF-α, IL-1β, and MCP-1) were expressed more in facet joints than the other tissues in patients with DLS; therefore, the etiology of inflammation might be more facet-centric. IL-19 and IL-20 induced proinflammatory cytokine expression in disc cells and might play a role in the pathogenesis of DLS.